Onboard, don’t orient, new faculty - JACQUELINE KRESS (Academic Chairpersons Conference Proceedings, 2020)
Each year 50,000 highly educated, accomplished people with no preparation for most of the tasks that comprise college faculty work will be hired. Typical orientation programs do not meet their needs to provide useful, timely information and skill-building. Onboarding programs are more effective, and the benefits go beyond the faculty.
Keywords: faculty orientation; faculty development; new faculty needs; faculty roles; faculty work life balance; faculty stress